A Process for Error Correction for Strength and Conditioning Coaches. Issue 6 (December 2017) - Cushion, Emily; Howe, Louis; Read, Paul; Spence, Adam
Abstract : ABSTRACT: THERE ARE SEVERAL SKILL ACQUISITION STRATEGIES AVAILABLE TO COACHES WHEN CORRECTING A MOVEMENT ERROR. HOWEVER, IT IS NOT ALWAYS CLEAR WHICH STRATEGIES SHOULD BE USED FOR A SITUATION AND IN WHAT ORDER. THIS ARTICLE AIMS TO PROVIDE COACHES WITH A LOGICAL EVIDENCE-BASED PROCESS TO ASSIST THEIR COACHING PRACTICE. IN ADDITION TO A PROPOSED MODEL OF ERROR CORRECTION, EXAMPLES ARE PROVIDED FOR SEVERAL COMMONLY OCCURRING SITUATIONS IN STRENGTH AND CONDITIONING PRACTICE.